2021
DOI: 10.3390/polym13132183
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial Polymeric Composites with Embedded Nanotextured Magnesium Oxide

Abstract: Nanotextured magnesium oxide (MgO) can exhibit both antibacterial and tissue regeneration activity, which makes it very useful for implant protection. To successfully combine these two properties, MgO needs to be processed within an appropriate carrier system that can keep MgO surface available for interactions with cells, slow down the conversion of MgO to the less active hydroxide and control MgO solubility. Here we present new composites with nanotextured MgO microrods embedded in different biodegradable po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 40 publications
0
11
0
Order By: Relevance
“…While significant research has focused on organic antimicrobial polymeric composites, inorganic particles have also been incorporated for antimicrobial purposes. Silver and copper are the most commonly used metallic antimicrobial agents taken the form of silver or copper micro/nanoparticles though recent research has also used various oxide particles such as zinc oxide, or magnesium oxide 50 . Generally, these particles release their respective metal ions that penetrate the cell and disrupt functions.…”
Section: Strategies For Developing Antimicrobial Polymer Compositesmentioning
confidence: 99%
“…While significant research has focused on organic antimicrobial polymeric composites, inorganic particles have also been incorporated for antimicrobial purposes. Silver and copper are the most commonly used metallic antimicrobial agents taken the form of silver or copper micro/nanoparticles though recent research has also used various oxide particles such as zinc oxide, or magnesium oxide 50 . Generally, these particles release their respective metal ions that penetrate the cell and disrupt functions.…”
Section: Strategies For Developing Antimicrobial Polymer Compositesmentioning
confidence: 99%
“…At the molecular level, magnesium ions are involved in various enzymatic reactions in cells and can indirectly encourage cell mineralization by increasing the activity of alkaline phosphates (C. Feng et al., 2017 ; Lin et al., 2018 ; Park et al., 2010 ; Serre et al., 1998 ; Tarafder et al., 2013 ). In addition, it has been shown that the incorporation of MgO into PLA can significantly increase the activity of osteoblasts and can effectively inhibit the value-added of osteoclasts, providing a good physiological basis for bone regeneration, in addition to the powerful antibacterial activity that MgO provides to PLA( Aničić et al., 2021 ). Other common dopants of PLA composites are ZnO and CuO, among others.…”
Section: Introductionmentioning
confidence: 99%
“…Although drug-induced antimicrobial strategies are still the most effective and widely used approach in clinical applications, bacterial resistance remains a major challenge. For example, an ion-mediated antibacterial strategy can achieve a good antibacterial effect due to its ability to continuously release antibacterial ions, such as copper [ 18 ] and magnesium [ 19 ]. As the ions used in this strategy are mostly heavy metals, it faces biosafety risks and great obstacles to clinical application [ 17 ].…”
Section: Introductionmentioning
confidence: 99%